The Digital Transformation Process in Encouraging the Internationalization of MSMEs: The Role of Digital Literacy as a Key Supporter - Selvia Linggani; Wanda Nadzirotul Hamidah (HARAMAIN: Jurnal Manajemen Bisnis, 2026)
This study investigates the digital transformation process in encouraging the internationalization of micro, small, and medium enterprises (MSMEs), with a particular focus on the role of digital literacy as a key supporting factor. Employing a qualitative case study approach, the research was conducted in Jember, Indonesia, involving MSME actors across various sectors. Data were collected through in-depth interviews, observations, and documentation, and analyzed using an interactive model consisting of data condensation, data display, and conclusion verification. The findings reveal that digital transformation among MSMEs often begins with basic adoption of digital tools; however, its effectiveness in supporting internationalization is highly dependent on the level of digital literacy. MSMEs with higher digital literacy demonstrate more strategic use of digital platforms, enabling them to access broader markets, including international customers. Conversely, limited digital literacy results in suboptimal utilization of technology and restricts market expansion. This study contributes theoretically by integrating digital literacy into the digital transformation framework as a central enabler of MSME internationalization, particularly within the context of developing regions. Practically, the findings highlight the importance of capacity-building initiatives, suggesting that policymakers and stakeholders should prioritize digital literacy development alongside technological infrastructure. The study is limited by its qualitative design and localized scope; therefore, future research is recommended to employ broader and comparative approaches. Overall, this research underscores the critical role of digital literacy in maximizing the impact of digital transformation for sustainable MSME growth in the global economy.